2017
DOI: 10.3390/ijerph14101232
|View full text |Cite
|
Sign up to set email alerts
|

Design of Research on Performance of a New Iridium Coordination Compound for the Detection of Hg2+

Abstract: Heavy metal pollution has become one of the most significant pollution problems encountered by our country in terms of environment protection. In addition to the significant effects of heavy metals on the human body and other organisms through water, food chain enrichment and other routes, heavy metals involved in daily necessities beyond the level limit could also affect people’s lives, so the detection of heavy metals is extremely important. Ir (III) coordination compound, considered to be one of the best ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…In agricultural research, an active real and realistic model is needed, and the model can truly reflect reality, which has a better support for reasoning and decision-making. Relying on complex algorithms to draw a model is the research direction and results of many researchers, but the development of the three-dimensional engine is not exactly the same; more is based on the support of the previous layer of software [15][16][17][18][19]. Augmented reality technology cross connects the real world and the virtual world by superimposing the virtual information collected by the computer so that the user can obtain the entity information that is difficult to obtain in the original environment, in the virtual world of computer simulation.…”
Section: Technology Implementation Of Vr Animation Platformmentioning
confidence: 99%
“…In agricultural research, an active real and realistic model is needed, and the model can truly reflect reality, which has a better support for reasoning and decision-making. Relying on complex algorithms to draw a model is the research direction and results of many researchers, but the development of the three-dimensional engine is not exactly the same; more is based on the support of the previous layer of software [15][16][17][18][19]. Augmented reality technology cross connects the real world and the virtual world by superimposing the virtual information collected by the computer so that the user can obtain the entity information that is difficult to obtain in the original environment, in the virtual world of computer simulation.…”
Section: Technology Implementation Of Vr Animation Platformmentioning
confidence: 99%
“…By analyzing the behavioural characteristics of Twitter users, Ma et al found that highly extroverted users tend to relieve their emotions through social tools more than other users, linking the emotions of highly extroverted users to their behaviors and providing a new entry point for analyzing user behavior: user emotions [7]. Based on the results, Ma and Tsai further analyzed user behavior on the Twitter platform and concluded that the user's personality and individuality could be analyzed and predicted by the user's online behavior patterns [8]. In studying the characteristics and changes of the user's emotional state, Polyakova et al found that the user's emotional state changed over time [9].…”
Section: Current Status Of Researchmentioning
confidence: 99%
“…More than 20% of the per capita net income of farmers in the key counties of economic forestry is from economic forestry income [4]. Increasing the supply of economic forestry products can not only effectively solve the contradiction of China's food and oil competition for land, provide natural, nutritious, safe, and high-quality products for the market, and meet the consumption demand of social residents for high-quality products after the upgrading of consumption but also effectively improve the income of rural farmers, especially in mountainous areas, promote the harmonious development of urban and rural society, and improve the overall competitiveness of the country [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%